Collaborative Provision of Graduate Education in CLMV: Case of Thailand’s Private Universities - Lavanchawee Sujarittanonta; Kittichok Nithisathian; John C. Walsh (Journal of Education and Vocational Research, 2016)
Education entails investments in time and money from the students and, therefore, the choices of degree programs and university names are critical for students and their future careers. The demand for foreign education in the CLMV (i.e. Cambodia, Lao PDR, Myanmar and Vietnam) market is fast expanding, especially for international graduate programs. Equipped with foreign degrees, the human resources of the host CLMV countries are ready for international jobs with international standards. This situation attracts investments by foreign universities to enter CLMV countries to offer degree programs, such as MBA, MPA and PhD. While Western universities are internationally recognized, the success of Asian universities operating within CLMV has not been studied. Consequently, this paper reports on research examining the success of Thai private universities that operate in CLMV countries, in particular Mynmar, which has only recently opened up to the world, as well as the developing prospects for Vietnam. Lao PDR and Cambodia. Data is collected through in-depth interviews of managers and students of international partner institutions of the host countries, through which Thai universities offer graduate degree programs. It is found that private Thai degree programs are welcomed in CLMV countries, while Thai degrees are favored over international Western degrees in terms of economic affordability and preferred over Chinese degree programs due to the socio-cultural perception that Chinese products are doubtful in quality. This is not surprising, considering that a 2014 study by the UNESCO Institute for Statistics (UIS) reported that among middle-income countries of Asia, Thailand and Malaysia lead the region when it comes to providing graduate education.